Does childhood bullying lead to the development of psychotic symptoms? A meta-analysis and review of prospective studies. Issue 1 (2nd January 2016) - Cunningham, Twylla; Hoy, Katrina; Shannon, Ciaran
Abstract : Purpose: Researchers have demonstrated associations between trauma and psychosis. Childhood trauma, in particular, appears to be an important determinant. Recently, bullying has become considered a traumatic experience in its own right. This review aims to analyse research with prospective designs, which will enable conclusions about whether or not bullying causes psychosis. Methods: A systematic review of the literature was carried out independently by two reviewers. Eligibility and quality assessment criteria were applied. A meta-analysis and narrative synthesis were then completed. Results: Ten studies met inclusion criteria. Four used data from the same large database, and were combined as one. The majority provided confirmation that bullying appears to cause later development of psychosis. A meta-analysis yielded an unadjusted odds ratio (OR) of 2.148 [95% confidence interval (CI) 1.140–4.044]. Conclusions: The studies reviewed here suggest that bullying does predict the later development of psychotic symptoms. What is lacking from the literature is adequate investigation into other potential mediating factors. The current review highlights the significant role of bullying within this complex interaction. Potential mediating variables are explored, including a dose–response effect for the severity and frequency of victimization. Suggestions for targeting intervention are also suggested alongside clinical implications and recommendations for future research.